A Study on Trends in the Rainfall Pattern over India: Examining temporal and spatial rainfall patterns in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
New month to month, regular and annual rainfall time arrangement of 36 meteorological subdivisions of India were built utilizing the month to month rainfall information for the fixed network of 1476 downpour check stations. In the new network, on a normal, there is one downpour check station for each 3402 Sq. km region. The new rainfall arrangement is transiently just as spatially homogenous. Linear trend investigation was completed to look at the long haul trends in rainfall over various subdivisions and month to month commitment of every one of the monsoon months to annual rainfall. During the south-west monsoon season, three subdivisions viz. Jharkhand, Chattisgarh, Kerala indicated significant diminishing trend and eight subdivisions viz. Gangetic WB, West UP, Jammu and Kashmir, Konkan and Goa, Madhya Maharashtra subdivision, Rayalseema, Coastal AP and North Interior Karnataka demonstrated significant expanding trends. It has been discovered that the commitment of June, July and September rainfall to annual rainfall is diminishing for couple of subdivisions while commitment of August rainfall is expanding in couple of different subdivisions. EOF examination is additionally done to know the spatial conveyance of rainfall.